2014
DOI: 10.1016/j.icarus.2014.01.033
|View full text |Cite
|
Sign up to set email alerts
|

The geology of the Marcia quadrangle of asteroid Vesta: Assessing the effects of large, young craters

Abstract: a b s t r a c tWe used Dawn spacecraft data to identify and delineate geological units and landforms in the Marcia quadrangle of Vesta as a means to assess the role of the large, relatively young impact craters Marcia ($63 km diam.) and Calpurnia ($53 km diam.) and their surrounding ejecta field on the local geology. We also investigated a local topographic high with a dark-rayed crater named Aricia Tholus, and the impact crater Octavia that is surrounded by a distinctive diffuse mantle. Crater counts and stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…Our absolute model age of Marcia can be compared only with those obtained in the same geologic unit and with the same functions. We found that our AMA of the Marcia ejecta blanket calculated with the functions of Schmedemann et al (in preparation) is just within the error estimates of the youngest AMA presented in the work of Williams et al (2014b) (101 ± 13 Ma versus 123 ± 9 Ma). We consider the counting area on the Marcia ejecta blanket to be more representative of the formation age than a counting area within the crater itself.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our absolute model age of Marcia can be compared only with those obtained in the same geologic unit and with the same functions. We found that our AMA of the Marcia ejecta blanket calculated with the functions of Schmedemann et al (in preparation) is just within the error estimates of the youngest AMA presented in the work of Williams et al (2014b) (101 ± 13 Ma versus 123 ± 9 Ma). We consider the counting area on the Marcia ejecta blanket to be more representative of the formation age than a counting area within the crater itself.…”
Section: Discussionsupporting
confidence: 86%
“…We consider the counting area on the Marcia ejecta blanket to be more representative of the formation age than a counting area within the crater itself. The latter counting area, which is presented in Marchi et al (submitted for publication) and Williams et al (2014b), corresponds to a possible impact melt pond. Thus, the derived age of the pond could be underestimated due to target property effects as observed on the Moon and Mars (e.g., Dundas et al, 2010;Hiesinger et al, 2012;van der Bogert et al, 2010van der Bogert et al, , 2013.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Williams et al (2014) focus on the stratigraphic relations of the large, young fresh craters and associated dark ejecta field found in the Av-8 (Marcia) quadrangle, and Buczkowski et al (2014) focus on the diversity of units on the highland of Vestalia Terra in Av-9 (Numisia) quadrangle. Garry et al (2014) have used the geologic map of the Av-10 (Oppia) quadrangle to investigate the stratigraphic relations and the context of high-albedo crater ejecta surrounding Oppia crater, building on the study of Le Corre et al (2013).…”
Section: Da Williams Et Al / Icarus XXX (2014) Xxx-xxxmentioning
confidence: 99%